2009
DOI: 10.1111/j.1755-3768.2008.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Bicanalicular double silicone intubation in external dacryocystorhinostomy and canaliculoplasty for distal canalicular obstruction

Abstract: . Purpose:  We aimed to evaluate the effectiveness of bicanalicular double silicone intubation in dacryocystorhinostomy (DCR) and canaliculoplasty for distal or common canalicular obstruction. Methods:  We reviewed the medical records of patients with distal or common canalicular obstruction who had undergone bicanalicular double silicone intubation (insertion of two tubes into each canaliculus) during external DCR and canaliculoplasty. We reviewed the records of subjects who had undergone the same surgery wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 12 publications
1
35
0
1
Order By: Relevance
“…Tables 5 and 6 summarize the tuberelated complications in the present study and the complications associated with previous double silicone stenting studies. Compared with the single-stent group, no significant complications appeared, which was consistent with previous reports [11][12][13][14][15]. The other treatment methods implicated for canalicular obstruction are DCR combined with membranectomy [5,6], trephination and silicone tube stenting [7,16], ballooning with/without silicone stenting [17,18], ballooning canaliculoplasty following lacrimal trephination [8], and intraoperative use of mitomycin C [9,10].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Tables 5 and 6 summarize the tuberelated complications in the present study and the complications associated with previous double silicone stenting studies. Compared with the single-stent group, no significant complications appeared, which was consistent with previous reports [11][12][13][14][15]. The other treatment methods implicated for canalicular obstruction are DCR combined with membranectomy [5,6], trephination and silicone tube stenting [7,16], ballooning with/without silicone stenting [17,18], ballooning canaliculoplasty following lacrimal trephination [8], and intraoperative use of mitomycin C [9,10].…”
Section: Discussionsupporting
confidence: 85%
“…In this report, a larger-diameter stent maintained a better separation of the lacrimal channel walls, which would be expected to decrease the chance of restenosis following stent removal. Similarly, double silicone tube stenting, as a method of widening dilation, has been suggested in several reports [12][13][14][15]; the clinical outcomes of these reports following double silicone tube intubation are summarized in Table 6. Two of them are cases with partial nasolacrimal duct obstruction (NLDO) or persistent congenital NLDO, and the patients received only double silicone intubation without DCR surgical procedure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…External DCR with membranectomy and double silicone intubation has been reported, with anatomic and functional success rates of 91-95% and 83-87%, respectively, compared with single-stent intubation of 75 and 70%, respectively. 4,25 Canalicular trephination with subsequent intubation is widely used for obstructions of the distal and common canaliculus as an office based intervention, with Sisler reporting success rates of 83% in 18 cases. 6 The success of the technique is largely based on the site of the obstruction, with Khoubian reporting 66% complete relief in cases of distal lower canalicular obstructions (5-10 mm from the punctum), to 59% complete relief in cases of CCO (410 mm from the punctum) when treated with trephination and intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Some techniques can be performed in an office setting, while others are used as an adjunct to more invasive lacrimal surgery. [2][3][4][5][6][7][8] In the setting of transnasal endoscopic dacryocystorhinostomy (EnDCR), one previous study has reported retrospective outcomes of trephination for CCOs. 9 To our knowledge, this is the first study that has employed membranectomy without trephination and has attempted to evaluate the outcome of both membranous and more solid distal obstructions of the common canaliculus.…”
Section: Introductionmentioning
confidence: 99%